Selective COX-2 inhibitor reduces bone healing in bone defects Inibidor seletivo de COX-2 reduz reparo em defeitos ósseos - Bruno César de Vasconcelos Gurgel; Fernanda Vieira Ribeiro; Marco Antônio Dias da Silva; Francisco Humberto Nociti Júnior; Antonio Wilson Sallum; Enilson Antônio Sallum; Sérgio de Toledo; Márcio Zaffalon Casati (Sociedade Brasileira de Pesquisa Odontológica, 2005)
Anti-inflammatory agents have been reported to regulate bone healing. The aim of this study was to investigate the effect of a selective cyclooxygenase-2 inhibitor (meloxicam) on bone healing in calvarial defects in rats. Thirty-six adult male Wistar rats were included. After anesthesia, a linear incision was made through the skin of the scalp, a full-thickness flap was reflected and a 4 mm round defect was made with a trephine drill. The animals were randomly assigned to one of the following 4 treatment groups (9 animals each), including daily subcutaneous injections: A: saline solution for 15 days; B: saline solution for 45 days; C: 3 mg/kg of meloxicam for 15 days and D: 3 mg/kg of meloxicam for 45 days. The animals were sacrificed and the specimens, routinely processed. The bone filling was histometrically measured and statistical analysis, performed. Intergroup comparisons demonstrated that the meloxicam groups presented a significant reduction in bone healing when compared to their respective controls (group A, 44.5 ± 5.75%, against group C, 57.5 ± 7.25%, p < 0.05; group B, 40.25 ± 13.75%, against group D, 52.25 ± 17.25%). Within the limits of the present study, it can be concluded that selective cyclooxygenase-2 inhibitors may reduce bone healing in calvarial defects in rats after continuous administration. Agentes antiinflamatórios têm sido descritos como reguladores do reparo ósseo. O objetivo deste estudo foi investigar o efeito de um inibidor seletivo da cicloxigenase-2 (meloxicam) no reparo ósseo em defeitos de calvárias de ratos. Trinta e seis ratos machos Wistar foram incluídos no estudo. Após anestesia, incisão linear e rebatimento de retalho de espessura total, um defeito de 4 mm de diâmetro foi criado na calvária dos animais com broca trefina. Os mesmos foram aleatoriamente distribuídos em um dos 4 grupos de tratamento (9 animais por grupo), recebendo injeções subcutâneas diárias de: A: soro fisiológico por 15 dias; B: soro fisiológico por 45 dias; C: 3 mg/kg de meloxicam por 15 dias; D: 3 mg/kg de meloxicam por 45 dias. Os animais foram sacrificados e os espécimes rotineiramente processados. Medidas do preenchimento ósseo foram histometricamente realizadas e analisadas estatisticamente. Comparações intergrupos demonstraram que os grupos com meloxicam apresentaram uma redução significativa no reparo ósseo quando comparados com os respectivos grupos-controle (grupo A, 44,5 ± 5,75%, contra grupo C, 57,5 ± 7,25%, p < 0,05; grupo B, 40,25 ± 13,75%, contra grupo D, 52,25 ± 17,25%). Dentro dos limites do presente estudo, pode ser concluído que os inibidores seletivos da cicloxigenase-2 podem reduzir o reparo ósseo em defeitos em calvárias de ratos após sua administração contínua.